Evaluating the effectiveness and safety of acupuncture on serum uric acid in asymptomatic hyperuricemia population: a randomized controlled clinical trial study protocol - Yu, Ling-ling; Li, Chen-nan; Fang, Meng-yue; Ma, Yan; Wang, Bo; Lin, Feng-ping; Liu, Wen-hua; Tu, Sheng-hao; Chen, Zhe; Xie, Wen-xi; Zhang, Rui-yuan; Huang, Yao; et al. (Frontiers in Endocrinology, 2023)
Background: The clinical harms of asymptomatic hyperuricemia to human health have become increasingly prominent. Previous studies have shown the potential benefits of acupuncture on uric acid levels in the body. However, definitive evidence is lacking. Our objective is to evaluate the efficacy and safety of acupuncture on serum uric acid (SUA) in asymptomatic hyperuricemia population. Methods: This is a randomized, single-blind, sham-controlled trial. 180 eligible patients with asymptomatic hyperuricemia will be recruited at three hospitals in China. Patients will be randomly assigned in a 1:1 ratio to receive 16 sessions of manual acupuncture or sham acupuncture for 8 weeks. Patients will be followed for 12 weeks. The primary outcome will be the change in SUA levels at week 8 after randomization. Secondary outcomes will be include dynamic changes in SUA levels, effective rates, proportion of gout flare, body weight, and acute medication intake. The MGH Acupuncture Sensation Scale (MASS) and adverse events related to acupuncture will be measured after each treatment. Blinding assessment will be performed on patients received at least one session of acupuncture. Data analyses will be performed on a full analysis set (FAS) and a per-protocol set (PPS). Ethics and Dissemination: Ethics approval has been obtained from the Clinical Trial Ethics Committee of Tongji Medical College, Huazhong University of Science and Technology (approval no: 2021-S135). Written informed consent will be obtained from enrolled patients. The findings will be disseminated in a peer-reviewed journal.